Internet - technical developments and applications 2 - Tkacz, Ewaryst; Rostanski, Maciej; Kapczynski, Adrian (Advances in Intelligent and Soft Computing, 2012)
The unusual direct progress of civilization in many fields concerning technical sciences is being observed in the period of last two decades. Experiencing extraordinary dynamics of the development of technological processes, particularly in ways of communicating, makes us believe that  the information society is coming into existence. Having the information in today's world of changing attitudes and socio-economic conditions can be perceived as one of the most important advantages. The content of this book is divided into four parts: ·         Mathematical and technical fundamentals, ·         Information management systems and project management ·         Information security and business continuity management ·         Interdisciplinary problems This monograph has been prepared to contribute in a significant way to the success of implementing consequences of human imagination  into social life. The authors believe that this monograph will influence the further technology development regarding IT with constantly expanding spectrum of its applications.